Disparity in Coronary Artery Diameter in Diabetic and Nondiabetic Subjects undergoing Percutaneous Coronary Intervention in Bangladesh: A 2-Year Retrospective Analysis - Kabir, CM Shaheen; Haq, M Maksumul; Cader, F Aaysha (Bangladesh Heart Journal, 2017)
Objective: Coronary arteries in diabetic patients were found to be narrower than in non-diabetic subjects. The aim of the study was to compare the coronary arteries diameter between diabetic and non-diabetic patients undergoing percutaneous coronary intervention (PCI) using stent diameter for greater accuracy. Methods: This was a randomized observational study. From a dedicated database, we retrospectively analysed all consecutive patients of both gender who underwent PCI in the cardiac catheterization laboratory of Ibrahim Cardiac Hospital and Research Institute, Dhaka, Bangladesh, from January 2011 to December 2012. Patients who required left main coronary artery stenting were excluded from this study. Patients were divided into two groups; diabetics and non-diabetics. We calculated the coronary artery diameter according to the diameter of the stent, achieved at the final pressure at which the stent was deployed. The diameter which was achieved at a given atmospheric pressure was taken from the attached booklet provided with the stent packaging. If post dilatation was required then the diameter achieved by the non-compliant balloon after post dilatation was taken as the reference diameter of the artery. Results: A total of 571 patients, 333 in diabetic and 238 in non-diabetic group were included in the study. Proximal segments of left anterior descending (LAD) coronary artery in diabetics and non-diabetics were 2.99±0.44 vs 3.14±0.50 mm (p=0.00) while mid and distal segments were 2.90±0.38 vs 3.10±0.42 mm (p=0.00) and 2.25±0.39 vs 2.42±0.45 mm (p=0.00) respectively. Various segments of proximal left Circumflex (LCx) coronary artery in diabetics and non-diabetics were 2.98±0.21 vs 3.01±0.25 mm (p=0.39) while distal circumflex were 2.35±0.40 vs 2.49±0.43 mm (p=0.00) respectively. Proximal segments of right coronary artery (RCA) in diabetic and nondiabetics were 3.0±0.28 vs 3.28±0.25 mm (p=0.00) while mid and distal segments were 2.97±0.26 vs 3.19±0.25 mm (p=0.00) and 2.43±0.51 vs 2.87±0.32 mm (p=0.00) respectively. The number of stents (1.34±0.87 vs 1.30±0.65; p=0.40) and type of stent utilized (DES & non DES: 87.3 & 12.7% vs 85.2 & 14.8%; p=0.50) between diabetic & non-diabetic groups were not significantly different; however the total stent length (23.1±13.3 vs 21.5±9.52 mm; p=0.03) in diabetic group was significantly longer. Conclusions: The diameter of LAD, distal circumflex and right coronary arteries were significantly narrower in diabetic than non-diabetic subjects. Bangladesh Heart Journal 2017; 32(1) : 23-28